The effect of introducing Pediatric Emergency Care Applied Research Network rule on reducing brain computed tomography use for children with minor head injury - Sung Wun Jung; Jae Ho Jang; Jin Seong Cho; Sung Youl Hyun; Yong Su Lim; Hyuk Jun Yang; Jea Yeon Choi (Pediatric Emergency Medicine Journal, 2019)
Purpose Computed tomography (CT) scan is an effective modality for detecting fatal traumatic brain injury. However, radiation exposure from CT can increase the risk of cancer, and children are more vulnerable to radiation than adults. We aimed to investigate the effect of introducing the Pediatric Emergency Care Applied Research Network (PECARN) rule to the emergency department (ED). Methods Medical records of children younger than 2 years with minor head injury who visited ED from January 2013 to June 2015 were reviewed. We started the education of radiation hazard and the PECARN rule in January 2014. The children were divided into pre- and post- education groups. The baseline characteristics, CT rate, and clinical outcomes were analyzed. The safety and efficacy of CT were defined as patients who received head CT scan per those experiencing clinically important traumatic brain injury (ciTBI) and patients without CT scan per those without ciTBI, respectively. Results Of 911 patients, 360 (39.5%) visited during the post-education period. Median age was 16.0 months (interquartile range, 11.0-20.0 months), and boys accounted for 58.5%. CT rate was reduced from 40.5% to 12.8% (P < 0.001). There was no difference in ciTBI rates between the two groups (1.3% vs. 1.7%, P = 0.622). The safety was 100% in both periods and the efficacy increased from 52.9% to 88.7%. Conclusion We have seen a significant decrease in CT rate through the education of the PECARN rule. After its introduction, CT use was reduced, and the efficacy was improved without decrease in the safety.